Die Kartierung des Kraftstoffverbrauchs - Zusätzliche Informationsgrundlage für den präzisen Ackerbau - Schutte, Benjamin; Herrmann, Ludger; Schreiber, Matthias; Kutzbach, Heinz Dieter (agricultural engineering.eu, 2004)
Mapping fuel consumption can be a precision farming method, in order to gather information on soil variability. Without additional sensors, data about real fuel consumption can be collected from the communication system of modern tractors (CAN Bus). In the measurements presented, the mapping was evaluated in terms of the tillage draught force needed and soil type differences. In additional experiments fuel consumption from the CAN bus was compared with the measured data consumption data.